Design thinking for commercial street architecture between sustainability techniques and local identity - Riham Hagag; Zeinab Feisal; Alaa Eleshy; Mamdouh Abdelsattar (Journal of Engineering and Applied Science, 2025)
Abstract This study presents a research perspective of the harmonious achievement of sustainability and local identity in commercial streets. It examines influence of sustainable techniques on local identity vocabulary in architectural design for commercial streets. This includes form developments, environmental relationships, design philosophy, and the method of gathering users and activities in the street. The study reveals how these factors contribute to the emergence of a new architectural design thinking characterized by “abstract identity.” This evolving role has introduced new models for interactive commercial streets that meet the requirements of the twenty-first century while preserving their local identity. Therefore, this paper explores how sustainability techniques and local identity aspects affect the development of design thought for commercial streets, aiming to finally devise a systematic strategy for designing future commercial streets that aligns with environmental requirements and preserves local identity.